Internet of Things and LoRa-based monitoring system on solar dryer dome for coffee drying - Amuddin, Amuddin; Sumarsono, Joko; Salman, Salman (Universitas Muhammadiyah Mataram, 2025)
Coffee drying is a critical stage in post-harvest processing to enhance product quality and market value. Karang Sidemen Village, Central Lombok, has significant potential to adopt renewable energy-based technology to support agricultural processing. This study aims to develop an Internet of Things (IoT) and LoRa-based monitoring system for solar dryer domes in the coffee drying process in Karang Sidemen Village, Central Lombok. The system integrates hardware and software to monitor temperature and humidity in real-time using SHT10 sensors, LoRa ESP32 modules, and the ThingSpeak platform. The method used is experimental to test the application of a temperature and humidity monitoring system on a solar dryer dome using IoT technology. The findings indicate that optimal drying occurs at temperatures between 50°C–55°C with low humidity, enhancing coffee product quality. The implementation of this technology reduces operational costs and supports sustainable agriculture through the utilization of renewable energy. The success in remote monitoring and power efficiency positions this system as an innovative solution for agricultural processing.